2015
DOI: 10.1111/fare.12117
|View full text |Cite
|
Sign up to set email alerts
|

An Extension and Moderational Analysis of the Family Stress Model Focusing on African American Adolescents

Abstract: model was tested longitudinally using structural equation modeling. Results showed that economic stress was associated with economic pressure and depressive symptoms among caregivers, which in turn was related to caregiver conflict. Higher levels of conflict had a negative influence on parenting quality at Wave 2, and this was linked to adolescent functioning. The depressive symptomology of secondary caregivers (SCs) exerted a greater indirect effect in the models than that of primary caregivers (PCs) and had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
73
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 36 publications
4
73
0
Order By: Relevance
“…As expected, neither caregiver's distress reached significance in predicting parenting when including negative couple behaviors and the other control variables. This is consistent with previous research reporting a mediating effect of caregivers' romantic relationship in linking caregiver depression and parenting (Conger et al, ; Landers‐Potts et al, ; Leinonen et al, ). Contrary to expectations, men's distress was not associated with men's couple interaction behaviors, precluding an indirect effect, and the indirect effect from mother's distress to father's parenting via the father's negative couple interactions was insignificant.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As expected, neither caregiver's distress reached significance in predicting parenting when including negative couple behaviors and the other control variables. This is consistent with previous research reporting a mediating effect of caregivers' romantic relationship in linking caregiver depression and parenting (Conger et al, ; Landers‐Potts et al, ; Leinonen et al, ). Contrary to expectations, men's distress was not associated with men's couple interaction behaviors, precluding an indirect effect, and the indirect effect from mother's distress to father's parenting via the father's negative couple interactions was insignificant.…”
Section: Discussionsupporting
confidence: 92%
“…Past research has established that parental depression is a risk factor for negative couple interactions as well as ineffective and negative parenting practices (Lovejoy et al, ; McMakin et al, ; Papp et al, ). There is further evidence that the impact of caregiver psychological distress on parenting may be indirect via increased negative interactions between romantic partners (e.g., Conger et al, ; Landers‐Potts et al, ). Few studies, take into account the behaviors of both caregivers in exploring these relations.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have replicated specific pathways of the Family Stress Model (Landers-Potts et al, 2015). For example, Landers-Potts et al (2015) found that economic stress was associated with economic pressure and symptoms of parental depression, which was associated with caregiver conflict.…”
Section: Introductionmentioning
confidence: 97%
“…For example, Landers-Potts et al (2015) found that economic stress was associated with economic pressure and symptoms of parental depression, which was associated with caregiver conflict. This conflict was negatively associated with parenting quality, which was linked to adolescent internalizing behavior and lower levels of positive adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…A consistent result is a heightened risk for mental health impairments, particularly elevated depressive symptoms [1, 2]. Contextual pathways from economic hardship to the development of depressive symptoms have been identified among African American youths.…”
mentioning
confidence: 99%